2012
DOI: 10.2478/v10098-012-0023-2
|View full text |Cite
|
Sign up to set email alerts
|

Isotopes of oxygen-18 and deuterium in precipitation in Slovakia / Izotopy kyslíka-18 A deutéria v zrážkach na Slovensku

Abstract: The article synthesizes available information on isotopic composition of precipitation in Slovakia (the Western Carpathians). Monthly δ 18 O data from eleven stations and period 1988-1997 were used to investigate correlations among the stations, altitude, air temperature and precipitation amount effects. The mean annual altitude and air temperature gradients of δ 18 O in precipitation were 0.21‰/100 m and 0.36‰/1°C, respectively. Maps of spatial distribution of mean annual δ 18 O in precipitation based on both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 18 publications
3
14
0
Order By: Relevance
“…2) showed the gradient of 0.16 % per 100 m of altitude, in accordance with the gradients previously described (Malík et al 1996;Holko et al 2012). This points to the fact that altitudinal effect still keeps some influence on oxygen isotopes distribution in springs' water, but is not the leading factor in this.…”
Section: Methodssupporting
confidence: 90%
See 2 more Smart Citations
“…2) showed the gradient of 0.16 % per 100 m of altitude, in accordance with the gradients previously described (Malík et al 1996;Holko et al 2012). This points to the fact that altitudinal effect still keeps some influence on oxygen isotopes distribution in springs' water, but is not the leading factor in this.…”
Section: Methodssupporting
confidence: 90%
“…This was derived from the average altitudinal dependency of d 18 O values found in springs (Fig. 2) and was found to be in accordance with the gradients previously described (Malík et al 1996;Holko et al 2012). In Eq.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…We interpret this increase in deuterium excess to reflect an 597 increase with elevation of the δ 0 value of meteoric precipitation falling on the surface 598 above these three caves. Other studies have shown similar increases although the 599 magnitude of the increase varies widely between sites (Holko et al, 2012;Gonfiantini et 600 al., 2001). The reason for these increases is not well understood.…”
Section: Correlation Between δ 18 O and δD 576mentioning
confidence: 56%
“…In all these cases C e was represented by the isotopic composition of rainfall sampled at high elevation, which was isotopically lighter than both C t and C p . End-members for all events are plotted together with the global and local meteoric water lines in Figure 8 O+10.62), constructed for mountain precipitation (Holko et al, 2012b) differs only slightly from the global line. The position of samples with respect to the local meteoric water line shows that several precipitation samples in both catchments were evaporated, i.e.…”
Section: P a P E R A C C E P T E D P R E -P R I N T V E R S I O Nmentioning
confidence: 99%